Word recall is affected by surrounding metrical context. Issue 3 (2nd April 2020) - Kimball, Amelia E.; Yiu, Loretta K.; Watson, Duane G.
ABSTRACT: It has been claimed that English has a metrical structure, or rhythm, in which stressed and unstressed syllables alternate. In previous research regular, alternating patterns have been shown to facilitate online language comprehension. Expanding these findings to downstream processing would lead to the prediction that metrical regularity enhances memory. Research from the memory literature, however, indicates that regular patterns are less salient and therefore less well remembered, and strings of similar sounds are harder to remember. This work suggests that, like lists of words with similar sounds, lists of words with similar metrical patterns would be less accurately remembered than comparable metrically irregular patterns. This study investigates these conflicting predictions by examining metrical regularity in a recall task. We find that words are better recalled when they do not match their metrical context, suggesting a regular metrical structure may not be beneficial in all contexts.